Significance of oxygen carriers and role of liquid paraffin in improving validamycin A production. (1st October 2016) - Feng, Jinsong; Jiang, Jing; Liu, Yan; Li, Wei; Azat, Ramila; Zheng, Xiaodong; Zhou, Wen-Wen
Abstract: Validamycin A (Val-A) synthesized by Streptomyces hygroscopicus 5008 is widely used as a high-efficient antibiotic to protect plants from sheath blight disease. A novel fermentation strategy was introduced to stimulate Val-A production by adding oxygen carriers. About 58 % increase in Val-A production was achieved using liquid paraffin. Further, biomass, carbon source, metabolic genes, and metabolic enzymes were studied. It was also found that the supplementation of liquid paraffin increased the medium dissolved oxygen and intracellular oxidative stress level. The expression of the global regulators afsR and soxR sensitive to ROS, ugp catalyzing synthesis of Val-A precursor, and Val-A structural genes was enhanced. The change of the activities of glucose-6-phosphate dehydrogenase and glyceraldehyde 3-phosphate dehydrogenase was observed, which reflected the redirection of carbon metabolic flux. Based on these results, liquid paraffin addition as an oxygen carrier could be a useful technique in industrial production of Val-A and our study revealed a redox-based secondary metabolic regulation in S. hygroscopicus 5008, which provided a new insight into the regulation of the biosynthesis of secondary metabolites.